Discursos e realidades do agronegócio: do PRODECER no cerrado brasileiro ao ProSAVANA no corredor de nacala em Moçambique - Catsossa, Lucas Atanásio (2017)
This work presented here has focused on the social and environmental aspects of ProSAVANA which are considered most sensitive and are mostly ignored by its executors once confronted with civil society organizations and certain scientific researches.The analisis is sustained through the contradictions managed by its “counterpart” in the Brasilian cerrado – PRODECER. The results leave clear evidences that there are many ambiguities and discursive contradictions within ProSAVANA since there are abrupt and successive discourses. This fact coupled with the general lack of transparency and clarity about the real motivations of its territorialization in the Nacala corridor leaves doubts on the ProSAVANA whether it being or not an inclusive program as argued by the official documents as the Master Plan on its “zero version”. It has been found out that ProSAVANA is as much an agricultural business rather than a true “lever” for promotion of development since it reflects much elite interests, that is, the interests of the bourgeoisie of the three countries involved than their communities. These findings are justified by the way in which the program has been conceived in which there was no space to allow local communities express their willings and opinions being then imposed the production mdel to follow. The doubts on the ProSAVANA as an inclusive program arise and get stronger when there has been observed situations of threats, intimidations and exclusion of civil society organizations, peasant associations and peasant themselves in the decision-making process perpertrated by its executer. It has been noted also that in addition to myth ProSAVANA presents several risks with serious territorial consequences. From a social point of view the myth of ProSAVANA are many including the solution to hunger and poverty, to be a source of both income and income generation for the affected families in the Nacala orridor. Assuming that the territorialization of capital does imply the deterritorialization of preexisting practices, the risk of the distruction of peasantry and those ones who practice it in the Nacala corridor is greater. From a territorial stand point the consequences are enormous which begins with its appropriation (for it is already cut) and then its specialization for production of commodities to serve the global market after which the territorial sovereignty shall be lost. Appropriation of territory by capital may lead to occurrence of several conflicts related to land use and natural resources as a whole. Given that most Nacala Corridor families rely not only on land for their survival but also use forests, wildlife, and rivers to obtain other income resources the risk of social convulsions is higher if these relations are broken. Even though its executers point out the PRAI (Best Agrarian Investment Practices) as a way to avoid conflicts they are not effective on the protectionism side for both peasants and the environment. The socio-environmental impacts are inevitable in this proposed production model for the agrarian development of the Nacala Corridor, such as the marginalization of peasants in the production process, as well as forest destruction and environmental degradation. Under contract agriculture that is seen by its executors as a strategy to promote such win-win (mutual gain) is also a farce, as it symbolizes the indirect entry of agribusiness into the peasant territories, it is a hidden way to undertake barbarism, that is to say, to exploit and expropriate the producer who is integrated with his scheme of production and above in his own territory.